Pengaruh Inflasi, BI Rate, dan Jumlah Uang Beredar terhadap Pertumbuhan Sukuk Korporasi - Mastura; Julia Ananda; Muhammad Yahya (Jurnal Investasi Islam, 2023)
This study aims to determine the effect of inflation, the BI rate, and the money supply on the growth of corporate sukuk in Indonesia. The research method used is a quantitative method using secondary data from 2015-2021 and multiple linear regression analysis. The results showed that inflation had a negative effect on the growth of corporate sukuk, the BI rate and the money supply had a positive effect on the growth of corporate sukuk. This study only uses 3 factors that influence the growth of corporate sukuk, among the many other contributing factors such as industrial production, exchange rates, oil prices and profit sharing of mudharabah deposits, and others. So the use of other variables for further research is highly recommended.